The distribution of cultivated species of Porophyllum (Asteraceae) and their wild relatives under climate change. Issue 6 (1st November 2016) - Estrada, Ana Susana; Ortiz, Enrique; VillaseÑor, JosÉ Luis; Espinosa-garcÍa, Francisco J.
Abstract : The geographic distribution of plant species is already being affected by climate change. Cropping patterns of edible plant species and their wild relatives will also be affected, making it important to predict possible changes to their distributions in the future. Currently, species distribution models are valuable tools that allow the estimation of species' potential distributions, in the recent past as well as during other time spans for which climate data have been obtained. With the aim of evaluating how species distributions respond to current and future climate changes, in this work species distribution models were generated for two cultivated species of the Porophyllum genus (Asteraceae), known commonly as 'pápalos' or 'pápaloquelites', as well as their Mexican wild relatives, at five points in time (21, 000 years ago, present, 2020, 2050, and 2080). Using a database of 1442 entries for 16 species of Porophyllum and 19 environmental variables, species distribution models were constructed for each time period using the Maxent modelling algorithm; those constructed for the future used a severe climate change scenario. The results demonstrate contrasting effects between the two cultivated species; for P. linaria, the future scenario suggests a decrease in distribution area, while for P. macrocephalum distribution is predicted to increase. Similar trends are observed in their wild relatives, where 11 species will tend to decrease in distribution area, while three are predicted to increase. It is concluded that the most important agricultural areas where the cultivated species are grown will not be greatly affected, while the areas inhabited by the wild species will. However, while the results suggest that climate change will affect the distribution of the cultivated species in contrasting ways, evaluations at finer scales are recommended to clarify the impact within cultivation zones.